Pericellular Ca2+ recycling potentiates thrombin‐evoked Ca2+ signals in human platelets. Issue 5 (11th October 2013) - Sage, Stewart O.; Pugh, Nicholas; Farndale, Richard W.; Harper, Alan G. S.
Abstract: We have previously demonstrated that Na + /Ca 2+ exchangers (NCXs) potentiate Ca 2+ signaling evoked by thapsigargin in human platelets, via their ability to modulate the secretion of autocoids from dense granules. This link was confirmed in platelets stimulated with the physiological agonist, thrombin, and experiments were performed to examine how Ca 2+ removal by the NCX modulates platelet dense granule secretion. In cells loaded with the near‐membrane indicator FFP‐18, thrombin stimulation was observed to elicit an NCX‐dependent accumulation of Ca 2+ in a pericellular region around the platelets. To test whether this pericellular Ca 2+ accumulation might be responsible for the influence of NCXs over platelet function, platelets were exposed to fast Ca 2+ chelators or had their glycocalyx removed. Both manipulations of the pericellular Ca 2+ rise reduced thrombin‐evoked Ca 2+ signals and dense granule secretion. Blocking Ca 2+ ‐permeable ion channels had a similar effect, suggesting that Ca 2+ exported into the pericellular region is able to recycle back into the platelet cytosol. Single cell imaging with extracellular Fluo‐4 indicated that thrombin‐evoked rises in extracellular [Ca 2+ ] occurred within the boundary described by the cell surface, suggesting their presence within the open canalicular system (OCS). FFP‐18 fluorescence was similarly distributed. These data suggest that upon thrombin stimulation, NCX activity creates a rise in [Ca 2+ ] within the pericellular region of the platelet from where it recycles back into the platelet cytosol, acting to both accelerate dense granule secretion and maintain the initial rise in cytosolic [Ca 2+ ]. Abstract : e00085 Abstract : We and others have previously reported that blocking the Na + /Ca 2+ exchanger (NCX) inhibits agonist‐evoked Ca 2+ signalling in human platelets. Surprisingly this inhibition occurs in the absence as well as the presence of extracellular Ca 2+ . Here we have investigated this phenomenon and provide evidence that the NCX plays a critical role in a pericellular Ca 2+ recycling system that enhances thrombin‐evoked Ca 2+ signals. In the light of these and previous findings, we put forward a new model of platelet Ca 2+ signalling. This suggests that the platelet membrane complex plays an analogous role in Ca 2+ signalling to the membrane nanojunctions previously characterised in arterial smooth muscle cells and cardiac myocytes.